2015
DOI: 10.1016/j.jgg.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/AKT Pathway and Renal Cell Carcinoma

Abstract: The phosphatidylinositol 3 kinase (PI3K)/AKT pathway is genetically targeted in more pathway components and in more tumor types than any other growth factor signaling pathway, and thus is frequently activated as a cancer driver. More importantly, the PI3K/AKT pathway is composed of multiple bifurcating and converging kinase cascades, providing many potential targets for cancer therapy. Renal cell carcinoma (RCC) is a high-risk and high-mortality cancer that is notoriously resistant to traditional chemotherapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
221
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(224 citation statements)
references
References 95 publications
(141 reference statements)
3
221
0
Order By: Relevance
“…The PI3k/Akt/mTOR protein cascade is one of the three major signaling pathways associated with receptor tyrosine kinases that have been identified in cancer cells [32]. Inhibition of PI3K isoforms, AKT, mammalian targets of rapamycin (mTOR), and other components in the pathway are being actively pursued for targeted cancer therapy [33]. It has been demonstrated that the VHL/HIF and PI3K/AKT pathways cross-talk extensively in a large signaling network, contributing to RCC [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3k/Akt/mTOR protein cascade is one of the three major signaling pathways associated with receptor tyrosine kinases that have been identified in cancer cells [32]. Inhibition of PI3K isoforms, AKT, mammalian targets of rapamycin (mTOR), and other components in the pathway are being actively pursued for targeted cancer therapy [33]. It has been demonstrated that the VHL/HIF and PI3K/AKT pathways cross-talk extensively in a large signaling network, contributing to RCC [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney cancer is the ninth most diagnosed cancer in the world . ccRCC, the most frequent kidney cancer, is associated with biallelic inactivation of the tumor suppressor gene VHL .…”
mentioning
confidence: 99%
“…In addition to these epigenetic regulators, many other gene mutations and somatic copy number aberrations (SCNA) have been associated with ccRCC. Alterations in PTEN , PI3Kca and mTOR are also prevalent in ccRCC, which are all key players in the PI3k–AKT–mTOR pathway regulating cell proliferation and HIF stabilisation . With regard to SCNA in ccRCC, 5q gains are the second most frequent alterations following 3p deletions with the SQSTM1 gene, thought to be the pathogenic target for this gain .…”
Section: Ccrcc Beyond Vhlmentioning
confidence: 99%